Pengenalan Dasar-Dasar Bahasa Inggris for Young Learners di Kelurahan Jawi-Jawi Kecamatan Bulukumpa - Azhar, Adzra Atifah; Danial; Harmilawati; Nurul Islamiah; Hasmiati (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIM Sinjai, 2022)
Abstract This community service program aims to introduce the basics of English for young learners at the Jawi-Jawi Village TK/TPA. The teaching method applied in this program is the fun learning method where the teacher creates a pleasant learning atmosphere. The results of this program can improve students' understanding and knowledge of the basics of English for young learners. This is evidenced by the results of the comparison of pre-test and post-test students where the average pre-test of students is 36% and the average post-test student is 83% so that the increase in student understanding and knowledge is 47% of the 30 student numbers. Keywords: Introduction, Basics of English, Young learners. Abstrak Program pengabdian kepada masyarakat ini bertujuan untuk mengenalkan dasar-dasar bahasa Inggris pada pelajar pemula di TK/TPA Kelurahan Jawi-Jawi. Metode pengajaran yang diterapkan dalam program ini yaitu metode fun learning dimana pengajar menciptakan suasana belajar yang menyenangkan. Hasil dari program ini dapat meningkatkan pemahaman dan pengetahuan siswa terhadap dasar-dasar bahasa Inggris pada pelajar pemula. Hal ini dibuktikan dari hasil perbandingan pre-test dan post-test siswa dimana rata-rata pre-test siswa adalah 36% dan rata-rata post-test siswa adalah 83% sehingga peningkatan pemahaman dan pengetahuan siswa adalah 47% dari 30 jumlah siswa. Kata kunci: Pengenalan, Dasar-dasar bahasa Inggris, Pelajar pemula.